2012
DOI: 10.2527/jas.2012-5099
|View full text |Cite
|
Sign up to set email alerts
|

Use of different levels of ground endophyte-infected tall fescue seed during heat stress to separate characteristics of fescue toxicosis1

Abstract: Studies of fescue toxicosis using whole seed diets show reduced feed intake and thermoregulatory ability, but much of the seed passes undigested through the animal. Cattle were fed ground tall fescue seed at different levels to potentially facilitate digestion and absorption of toxins and identify toxin sensitivity for major characteristics of the condition [i.e., hyperthermia, reduced feed intake (FI), reduced blood prolactin]. Steers (n = 18; 350 kg BW) were housed in the Brody Climatology Laboratory at ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…This allowed for equalization of dry matter intake among treatments. As mentioned previously, decreased intakes are commonly associated with cattle consuming E+ feedstuffs (Schmidt et al, 1982;Paterson et al, 1995;Spiers et al, 2012). Increased titer responses to vaccination against horse red blood cell and keyhole limpet haemocyanin have been reported in calves fed on a lower plane of nutrition (Pollock et al, 1994).…”
Section: Humoral Immunitymentioning
confidence: 90%
See 2 more Smart Citations
“…This allowed for equalization of dry matter intake among treatments. As mentioned previously, decreased intakes are commonly associated with cattle consuming E+ feedstuffs (Schmidt et al, 1982;Paterson et al, 1995;Spiers et al, 2012). Increased titer responses to vaccination against horse red blood cell and keyhole limpet haemocyanin have been reported in calves fed on a lower plane of nutrition (Pollock et al, 1994).…”
Section: Humoral Immunitymentioning
confidence: 90%
“…At the start of P2, ambient temperatures were set to cycle between 33.3°C during the day and 22.2°C at night. This was to simulate average temperature fluctuations experienced by cattle in Kentucky during July and August, when effects of fescue toxicosis are at their most severe (Hemken et al, 1981) and has been previously shown to be sufficient for inducing signs of fescue toxicosis in cattle during periods of tall fescue seed consumption (Spiers et al, 2012). Temperature humidity index (THI) was calculated as described by Hahn (1999): Increased THI conditions continued through P3, when heifers were provided their respective endophyte seed treatments.…”
Section: Feedstuffmentioning
confidence: 99%
See 1 more Smart Citation